2015
DOI: 10.1039/c5cc06144j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantification of starch molecular order through multivariate modelling of13C CP/MAS NMR spectra

Abstract: A partial least squares model has been generated enabling the rapid assessment of ordered molecular structure in a semi-crystalline polymer, starch, directly from solid state NMR spectra. Solid state NMR spectroscopy offers many advantages over conventional analysis tools being non-destructive and functional in complex mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The CP MAS 13 C NMR spectrum of native starch depicted in Figure shows the shape characteristic for semicrystalline starch. Three peaks at positions 101.6, 100.5, and 99.5 ppm in the C 1 resonance, typical for double helices packed in a monoclinic lattice (A‐type structure), were observed in this spectrum . The triplet corresponds to the three equivalent classes of six monomers creating the single helical turn, and is related to three distinct torsions about the α—(1‐4) linkage .…”
Section: Cp and Sp Mas 13c Nmr Spectramentioning
confidence: 83%
See 2 more Smart Citations
“…The CP MAS 13 C NMR spectrum of native starch depicted in Figure shows the shape characteristic for semicrystalline starch. Three peaks at positions 101.6, 100.5, and 99.5 ppm in the C 1 resonance, typical for double helices packed in a monoclinic lattice (A‐type structure), were observed in this spectrum . The triplet corresponds to the three equivalent classes of six monomers creating the single helical turn, and is related to three distinct torsions about the α—(1‐4) linkage .…”
Section: Cp and Sp Mas 13c Nmr Spectramentioning
confidence: 83%
“…The 13 C CP MAS NMR spectra measured for native starch and plasticized F‐TPS and S‐TPS samples depicted in Figure show four clearly resolved resonance lines associated with the six carbon nuclei in the starch monomer unit at ~101 ppm (C 1 ), ~83 ppm (C 4 ), ~73 ppm (C 2,3,5 ), and ~62 ppm (C 6 ) . One more resonance at the chemical shift of 167 ppm was observed in the spectrum of F‐TPS, which is associated with formamide carbon nuclei .…”
Section: Cp and Sp Mas 13c Nmr Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…The intensity peaks can be linked to the carbon positions of the glycosidic ring. Flanagan et al [20] found that the intensity peak C2, 3, 5 is asymmetric for native (i.e., semi-crystalline) starch, while approaches a symmetric shape for amorphous samples. Gaussian function-based deconvolution was carried out to quantify the asymmetry of this peak.…”
Section: C-nmr Spectroscopymentioning
confidence: 99%
“…There are two starch polymers biosynthesised during plant growth, namely amylose and amylopectin (Liu, Halley, & Gilbert, 2010;Jiang, Gao, Li, & Zhang, 2011). These two polymers can be organized on different scales in the starch granule to construct a multiscale supramolecular system; this system involves the whole granule, growth rings, blocklets, semicrystalline lamellae, crystallites, and double/single helices (Buleon, Colonna, Planchot, & Ball, 1998;Luengwilai & Beckles, 2009;Perez & Bertoft, 2010;Blazek & Gilbert, 2011;Doutch & Gilbert, 2013;Flanagan, Gidley, & Warren, 2015;Zhang et al, 2015). The structures with scales larger than that of lamellae can be loosely termed as 'large-scale' structures, including the growth rings and blocklets (Doutch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%